Math, asked by rahatanjum80615, 7 months ago

find the remainder when x³+3x²+3x+1 is divided by X + 1​

Answers

Answered by DevyaniKhushi
0
  • On dividing (x³ + 3x² + 3x + 1) by (x + 1), we get, no remainder or zero(0) remainder.

Verification :

 =  >  {x}^{3}  +  {3x}^{2}  + 3x + 1 \\  =  >   {x}^{3} +  {x}^{2} +  {2x}^{2}    + 2x + x + 1\\   =  > {x}^{2} (x + 1) + 2x(x + 1) + 1(x + 1) \\ =  >   (x + 1) \{ {x}^{2}  + 2x + 1 \} \\  =  >(x + 1) \{  {x}^{2}  + x + x + 1\} \\  =  > (x + 1) \{x(x + 1) + 1(x + 1) \} \\  =  > (x + 1) \{ (x + 1)(x + 1)\} \\  =  > (x + 1)(x + 1)(x + 1)

  • As the factors of (x³ + 3x² + 3x + 1), is (x + 1),(x + 1),(x + 1) thus, it is (x + 1)³
Answered by mansi003022
1

Answer:

hey mate here is ur answer

Step-by-step explanation:

by remainder theorem :

=> x+1=0 => x=-1

=>p(x)= x³+3x²- 3x-1p(-1)

=>(-1)³+3 (-1)²- 3(-1) -1

=>-1+3(1)+3-1

=> -1+3+3-1

=>6-2

=> 4

thus remainder is 4..

#pls mark me as brainaliest #

&# follow me #

Similar questions